Microcirculation‐on‐Chip: Application of Transmural Flow Across In Vitro Microvasculature Enables Direct Sampling of Interstitial Therapeutic Molecule Distribution (Small 46/2019). Issue 46 (13th November 2019) - Offeddu, Giovanni S.; Possenti, Luca; Loessberg‐Zahl, Joshua T.; Zunino, Paolo; Roberts, John; Han, Xiaogang; Hickman, Dean; Knutson, Charles G.; Kamm, Roger D.
Abstract : In article number 1902393, Charles G. Knutson, Roger D. Kamm, and co‐workers use microvascular networks self‐assembled from human cells within microfluid devices to directly measure trans‐capillary solute flux. Physiological fluid flow through the cell junctions, passive diffusion across the cell membrane, and active vesicular transport, recapitulate the in vivo mode and magnitude of transport for different types of therapeutic molecules.